Studies on phytochemical constituents and antioxidant activity of Alstonia scholaris - Mistry Dhruti; Parekh Bhavika; Pithawala Meonis (International Journal of Life Sciences, 2017)
The study aimed to evaluate and compare qualitatively and quantitatively phytochemical constituents present in bark, stem and leaves of the medicinal plant Alstonia scholaris. Qualitative phytochemical screening revealed the presence of alkaloids, saponins, terpenoids, flavonoids, phenolic compounds, tannins, steroids, and glycosides in bark, stem and leaf extracts. The glycosides, alkaloids, gums and mucilage were found in higher quantity in bark of A. scholaris as compared to that in stem and leaf. Further, in vitro antioxidant potential of extracts from bark of Alstonia scholaris was also analyzed. Both aqueous and/or methanolic extracts from bark of A. scholaris showed potent total antioxidant activity. At every concentration studied, percentage of superoxide radicals scavenged by aqueous extracts from bark of A. scholaris was higher even than those of standard gallic acid at respective concentrations. Similarly the results of DPPH free radical scavenging assay showed that aqueous extracts from bark of A. scholaris better scavenged free radicals than the methanolic extract from bark of A. scholaris as well as standard Ascorbic acid tested at respective concentrations.